Development and validation of a LC-MS/MS method for the simultaneous determination of simnotrelvir and ritonavir in human serum and bronchoalveolar lavage fluid - Xiaoyu Yang; Wanling Lin; Yushang Zhao; Chaoyue Zhao; Fei Zhou; Dong Wang; Zhihong Yue; Lin Pei; Mei Jia; Bin Cao; Lin-Lin Cao; Hui Wang (BMC Chemistry)
Abstract “Xiannuoxin” (simnotrelvir/ritonavir) is a novel anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) drug developed in China, which plays an antiviral role by inhibiting 3C-like protease (3CLpro). At present, it has been put into clinical use, while a simple, accurate and sensitive detection method is urgently needed for the quantification of simnotrelvir/ritonavir in human serum and bronchoalveolar lavage fluid (BALF) to ensure safe and efficacious antiviral therapeutics. In this study, we developed a liquid chromatography tandem mass spectrophotometry (LC-MS/MS) method for the simultaneous determination of simnotrelvir, ritonavir and urea concentrations in human serum and BALF samples. Prior to LC-MS/MS analysis, a user-friendly, one-step pre-analytical process was conducted, followed by a rapid chromatographic run lasting 3 min. This was then succeeded by positive and negative electrospray ionization and detection using a triple quadrupole tandem mass spectrometer in the multiple reaction monitoring mode. Subsequently, the LC-MS/MS method underwent a comprehensive validation in aspects such as sensitivity (LoQs of 2.5 ng/mL, 0.1 ng/mL, and 1 μg/mL for simnotrelvir, ritonavir and urea), linearity, carryover, precision, trueness (recovery rates of simnotrelvir, ritonavir and urea were between 85 and 115%), matrix effect (within 85-115%) and stability (stable for 72 h at room temperature). The validation results demonstrated that this LC-MS/MS method was robust and reliable. Notably, we can use the urea dilution correction method to calculate the concentrations of simnotrelvir and ritonavir in epithelial lining fluid (ELF), which is of great significance for evaluating the effectiveness and safety of antiviral drug treatment. Graphical Abstract